1986
DOI: 10.1288/00005537-198610000-00008
|View full text |Cite
|
Sign up to set email alerts
|

A systematic approach to the surgical management of acoustic neuroma

Abstract: Contemporary otomicrosurgical techniques have made total removal of acoustic tumor with preservation of the seventh and sometimes the eighth cranial nerves possible. The four approaches currently used in acoustic tumor surgery are the middle cranial fossa, the translabyrinthine, the suboccipital, and the combined translabyrinthine-suboccipital. This review examines the surgical results in the removal of more than 600 acoustic tumors and outlines a rationale for the choice of approach. Tumor size on computed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
72
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(78 citation statements)
references
References 9 publications
6
72
0
Order By: Relevance
“…In 1993, Glasscock et al 38 decried the "disarray of data" in the VS literature regarding outcome reporting. Although there are available standard metrics for reporting tumor size, hearing, and facial function, some authors do not adhere to these metrics, providing nonuniform data that are difficult to compare across studies.…”
Section: Limitations Of the Study And Future Directionsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 1993, Glasscock et al 38 decried the "disarray of data" in the VS literature regarding outcome reporting. Although there are available standard metrics for reporting tumor size, hearing, and facial function, some authors do not adhere to these metrics, providing nonuniform data that are difficult to compare across studies.…”
Section: Limitations Of the Study And Future Directionsmentioning
confidence: 99%
“…This approach may be poorly tolerated by the elderly, as extradural dissection of the adherent dura may be difficult. 85 The middle cranial fossa corridor is suggested for younger patients with smaller tumors 7,38,81 in the IAC with less involvement of the CPA, specifically the tumors that involve the fundus of the IAC, a location to which access and visualization are restricted during the retrosigmoid approach. 20 This route is also indicated for patients with useful preoperative hearing (although the definition of "useful" is still open to debate).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In two other large series, Sindou et al [6] and Knosp et al [7] reported a trigeminal and visual cranial nerve deficit incidence of between 14 and 58%. Similarly, even with microsurgical resection with intra-operative monitoring, facial nerve dysfunction occurs in up to 7% of patients [26][27][28][29] and hearing loss is universally observed in most acoustic neuromas exceeding 2-3 cm in diameter [30][31][32]. Hence, radiation therapy has been a preferred choice for such tumors with preserved neurological function.…”
Section: Hypofractionatedmentioning
confidence: 99%
“…4,36 For small and medium-sized tumors, long-term facial nerve preservation rates are reported to be more than 90%, but this rate is substantially lower for large tumors. 20,29 Series of large VSs frequently have been published as distinct clinical entities, because large tumors present a greater challenge to surgeons regarding total removal, cranial nerve preservation, and other postoperative complications. 32,49 Due to the paucity of data for such large tumors, a systematic literature review of all the available reports would be greatly beneficial in determining optiFacial nerve outcomes after surgery for large vestibular schwannomas: do surgical approach and extent of resection matter?…”
mentioning
confidence: 99%